MODELLING OF AVERAGE DRIFT SPEED OF ELECTRONS IN ONE-DIMENSIONAL STRUCTURE FROM GALLIUM ARSENIDE - V. N. Mishchenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Modeling results of average drift speed of electrons are given in one-dimensional structure from gallium arsenide. Recommendations about a choice of sizes of a temporary step and length of a spatial cell which define procedure of numerical modeling are developed.